Immigration Justice - Higgins, Peter (Edinburgh University Press, 2013)
Much philosophical work on immigration is founded on an outdated conception of immigrants and the causes of migration. This is based on the model of the pre-World War II European migrant to North America escaping political tyranny, fleeing famine or hoping to claim 'unsettled' land. Higgins draws on empirical evidence to show that the world has changed, and reasons for migration have changed too. So we need to create new moral principles for deciding which immigrants should be admitted. Rather than suggesting one absolute solution, Higgins argues that a unique set of immigration policies will be just for each country. He concludes with concrete recommendations for policymaking.